Dialectics of Educational Technology and Reposition of Islamic Religious Education: Teachers’ Role in Globalization Era - Agus Purwowidodo (Ta'dib: Jurnal Pendidikan Islam, 2016)
Learning technology as applied disciplines grows and evolves based to the needs of learning more effective, more efficient, more and more, more spacious, and more quickly in the globalization era. And also solves the problem, facilitating problem solving learning on design aspects, development, utilization, management, and assessment processes and sources in learning. Islamic religious education teachers challenge in the global era is the demands of the learning process that can improve informationliteracy that is well supported by data and facts to deliver to the students in the era of information society (information society) and the scientific community (knowledge society). So it is needed an approach and innovative methods of learning strategies that address the challenges of learning needs in the era of globalization and information. Dialectics of technology on learning in a globalization era are characterized by the demands of the students to have critical thinking skills, problem solving, innovative and creative, mastering ICT, fluent communication, and multi languages. And also Islamic religious education teachers’ competence and interaction and learning technologies such as ICT products that push reposition the role of an advanced teacher trainers, counselors, managers, participants, leader and author of learning works as an abstraction and a high commitment as a base quality of professionalism.Teknologi pembelajaran sebagai  disiplin ilmu terapan tumbuh dan berkembang sesuai kebutuhan belajar  lebih efektif, lebih efisien, lebih banyak, lebih luas, lebih cepat di era global. serta memecahkan, memfasilitasi pemecahan masalah belajar pada aspek desain, pengembangan, pemanfaatan, pengelolaan, dan penilaian proses-proses dan sumber-sumber untu belajar. Tantangan guru PAI di era global adalah tuntutan terhadap proses pembelajaran yang mampu meningkatkan information literacy yang baik didukung oleh data dan fakta untuk menghantarkan siswanya menuju pada era masyarakat informasi (information society) dan masyarakat ilmu pengetahuan (knowledge society). Sehingga di butuhkan bentuk pendekatan strategi dan metode inovatif pembelajaran yang mampu menjawab tantangan kebutuhan pembelajaran pada era globalisasi dan informasi. Dialektika teknologi terhadap proses pembelajaran di era global diwarnai dengan tuntutan terhadap siswa mempunyai keterampilan dalam berpikir kritis, memecahkan masalah, inovatif dan kreatif, menguasai ICT, komunikasi lancar, multi bahasa. Serta interaksi kompetensi Guru  PAI  dan produk teknologi pembelajaran berupa ICT yang mendorong reposisi peran guru menajdi pelatih, konselor, manajer, partisipan, pemimpin serta pengarang karya pembelajaran sebagai daya abstraksi dan komitmen yang tinggi sebagai basis kualitas profesionalisme.